Carbon black and chitin nanofibers for green tyres: preparation and property evaluation - Mathew, Mariya; Dominic, C. D. Midhun; Neenu, K. V.; Begum, P. M. Sabura; Dileep, P.; Kumar, T. G. Ajith; Sabu, Akshay Alax; Nagane, Dhiraj; Parameswaranpillai, Jyotishkumar; Badawi, Michael (Carbohydrate Polymers, 2023)
This research highlights the synergistic use of carbon black (CB) and chitin nanofibers (CHNFs) for developing green tyres for the first time. The CHNFs (12-30 nm) were prepared from chitin powder with the help of steam explosion and mild oxalic acid hydrolysis. The CHNFs were uniformly dispersed in natural rubber (NR) latex, dried, and mixed with CB in a two-roll mill to form NR/CB/CHNF composites. The NR/CB/CHNF composite at 1 phr CHNF loading exhibited tensile and tear strengths that were about 47 and 160 % greater than the NR-Neat, respectively. The dynamic mechanical analysis showed that the loss tangent (tan delta) at 60 degrees C was 50 % lower for the NR/CB/CHNF 1.0 composite than for the NR/CB50 composite. The study succeeded in developing a new green tyre tread formulation that would be helpful for attaining sustainability and a circular economy.
Keywords: carbon black; Chitin nanofibers; Green Tyre; natural rubber latex